Teachers’ Mindset and Readiness for Differentiated Mathematics Instruction: Case of Visually Impaired in Inclusive Classes - Sumbaji Putranto (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
Teachers play an important role in determining the successful implementation of differentiated mathematics instruction (DMI) in inclusive classes. This success is strongly influenced by teachers’ mindsets and their readiness to implement such instruction. This study aims to explore teachers’ mindsets and readiness regarding DMI for vissually impaired (VI) students in inclusive classes, as well as to examine the relationship between mindset and teacher readiness. The study used an explanatory sequential design, beginning with a quantitative phase followed by a qualitative phase. The quantitative phase utilized a questionnaire measuring teachers’ mindsets and readiness. The questionnaire consisted of 20 items with five response options and was reviewed by two experts to establish instrument validity prior to administration. The quantitative data were analyzed descriptively and correlationally using Pearson’s correlation test. The qualitative phase involved semi-structured interviews to further explain the quantitative findings. A total of 50 Indonesian mathematics teachers participated in the study and were selected through purposive sampling. The findings indicate that Indonesian mathematics teachers generally demonstrate a positive mindset and are prepared to implement DMI for VI students in inclusive classes. The results also reveal that teachers’ mindsets significantly influence their readiness to implement DMI. However, several teachers reported feelings of anxiety and stress related to implementing DMI in inclusive settings. These findings highlight the importance of continuous teacher engagement in professional development programs to enhance understanding of DMI and its effective implementation, particularly in supporting VI students in inclusive classes.